Serology for Helicobacter pylori compared with symptom questionnaires in screening before direct access endoscopy. Issue 3 (March 1995) - Mendall, M A; Jazrawi, R P; Marrero, J M; Molineaux, N; Levi, J; Maxwell, J D; Northfield, T C
Abstract : This prospective study aimed to compare serology for Helicobacter pylori with two, symptom questionnaires in screening patients before direct access endoscopy. Methods were compared in terms of the number of endoscopies saved and pathology missed in 315 patients referred to a gastroenterology unit by 65 local GPs. The serology used was based on an acid glycine extract of H pylori. One in-house questionnaire was based on the Glasgow dyspepsia (GLADYS) system and the other questionnaire was that reported by Holdstock et al. A cut off point of 6.3 U/ml for H pylori serology was selected for screening patients (97% sensitive and 75% specific). Serology was combined with a history of NSAID usage in determining who should have endoscopy. For the in-house questionnaire, a cut off score of more than 8 out of a possible maximum of 18 was chosen, after prior evaluation in 118 patients referred for direct access endoscopy (the sensitivity for detection of peptic ulcer was 88%, specificity 61%). A cut off score of more than 412 was used for the Holdstock questionnaire. In patients under 45 years, serology detected more peptic ulcers than the in-house questionnaire and the Holdstock questionnaire (27/28 v 24/28, NS and v 20/28, p < 0.05 respectively). The Holdstock questionnaire saved significantly more endoscopies than the other two methods (76/149 v 57/149 for the in-house questionnaire, p = 0.05 and 59/149 for serology, p = 0.05). In all age groups combined, serology was significantly better than the in-house and Holdstock questionnaires at detecting peptic ulcers and gastric cancer (61/63, 52/63, p<0.02, and 50/63, p<0.01 respectively). But serology saved significantly fewer endoscopies (89/315, 135/315, p<0.005, and 119/315, p<0.05 respectively). Serology was inferior to the Holdstock questionnaire at detecting severe oesophagitis. It is concluded that serology is the method of choice in screening before direct access upper gastrointestinal endoscopy in those under 45 years. It best combines a high sensitivity for peptic ulcer disease with a large reduction in unnecessary negative endoscopies.